2021
DOI: 10.1515/jafio-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Does the Contract Type Matter? Impact of Marketing and Production Contracts on Cashew Farmers’ Farm Performance in Ghana

Abstract: Many studies show that participation in contract farming has positive impacts on farm productivity and incomes. Most of the literature, however, does not take into account that contracts vary in their specifications, making empirical evidence scarce on the diverse impacts of different types of contracts. In this study, we investigate the driving forces of participation in marketing and production contracts, relative to spot markets. We also study the extent to which different contract types add additional bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Given these among other reasons, tree crops have attracted research attention in developing countries in the past few years. Studies on cash crops covered areas such as production ( Heidenreich et al., 2022 ; Rubhara et al., 2020 ), marketing ( Dubbert and Abdulai, 2021 ; Bannor et al., 2019 ) and commercialisation ( Komarek, 2010 ). These studies provided insights into the cash crop production system's dynamics, marketing strategies, commercialisation, and contribution to farmers' livelihoods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these among other reasons, tree crops have attracted research attention in developing countries in the past few years. Studies on cash crops covered areas such as production ( Heidenreich et al., 2022 ; Rubhara et al., 2020 ), marketing ( Dubbert and Abdulai, 2021 ; Bannor et al., 2019 ) and commercialisation ( Komarek, 2010 ). These studies provided insights into the cash crop production system's dynamics, marketing strategies, commercialisation, and contribution to farmers' livelihoods.…”
Section: Introductionmentioning
confidence: 99%
“…Every season, foreign investors and brokers trip to the country to aggregate raw cashew nuts for export ( Bannor et al., 2019 ). Given the importance of cashew production and trade in the country, researchers have explored the dynamics in cashew value chains, marketing and profitability to help provide insights and a possible roadmap to improve the sector ( Dubbert and Abdulai, 2021 ; Bannor et al., 2019 ). Though it was evident in the marketing of other commodities that the land tenure system and harvesting time influenced market participation, the same cannot be justified for the cashew sector in Ghana and Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Participating in emerging marketing channels is one way for Sub-Saharan Africa (SSA) to raise agricultural productivity, improve rural development, and reduce poverty. Small-scale farming structures, inadequate infrastructure, a lack of capital and technology, and high levels of information insecurity, on the other hand, restrict developing economies' agri-food sectors from competing in rapidly expanding markets (Dubbert and Abdulai, 2022). A contract farming (CF) system, in which a third party contracts crop output from farmers, has been touted as a strategy to enhance participation of developing countries in the global market (Adabe et al, 2019;Dubbert, 2019;Dubbert and Abdulai, 2022;Adaku and Amanor-Boadu, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale farming structures, inadequate infrastructure, a lack of capital and technology, and high levels of information insecurity, on the other hand, restrict developing economies' agri-food sectors from competing in rapidly expanding markets (Dubbert and Abdulai, 2022). A contract farming (CF) system, in which a third party contracts crop output from farmers, has been touted as a strategy to enhance participation of developing countries in the global market (Adabe et al, 2019;Dubbert, 2019;Dubbert and Abdulai, 2022;Adaku and Amanor-Boadu, 2021). The goals of CF, which is an institutional response to market uncertainty (Barrett et al, 2012;Adabe et al, 2019), are to boost investment in new production technologies (Pham et al, 2021), have effective value chain governance (Donovan et al, 2015), and supply quality inputs (Saenger et al, 2013;Kumar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that participation in contract farming constitutes an important vehicle in the transition to modern agriculture and significantly improves the living conditions of many smallholder farmers worldwide. It does not only enable smallholder farmers to overcome market and production barriers, and to sell their products on international markets, but also leads to higher yields, higher incomes, and to improved food security (Dubbert, 2019; Dubbert & Abdulai, 2021; Maertens & Velde, 2017; Minot & Sawyer, 2016; Ton et al, 2018; Wang et al, 2014).…”
mentioning
confidence: 99%